PENGEMBANGAN MODUL PADA MATERI SISTEM EKSKRESI BERBASIS HOTS DI KELAS - Harita, Radani Srindiani (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The type of research used in this research is research and development. The development model for this research uses a 4-D model of 4 stages according to Thiangrajan in Trianto (2009: 189. The analysis technique used is qualitative data in descriptive form which describes the validation, practicality and effectiveness of the teaching materials that have been prepared. From the results of the development carried out by researchers, the data obtained are the results of the validator (Lecturer) test with an average value of 85.9%, the results of practicality tests by teachers with an average value of 3.53%, practicality tests by students with an average of 3.45%, stated to be very practical, the test of student effectiveness during the learning process using the module was categorized as very effective, the results of student motivation with an average score of 89.57% in the very high category, and the observation test of student activities with an average score of 89.2% in the category very effective, and student learning outcomes in the cognitive domain show very good results. Thus. Conclusion: It can be concluded that the development of modules on human excretory system material is declared valid, practical and effective and can increase student motivation and learning outcomes. Therefore, suggestion: Researchers suggest that science subject teachers should be able to use learning modules as teaching materials in the teaching and learning process because they can simplify the teaching and learning process activities and can increase student motivation and learning outcomes.